Complex oscillatory redox dynamics with signaling potential at the edge between normal and pathological mitochondrial function - Kembro, Jackelyn Melissa (2014)
Fil: Kembro, Jackelyn Melissa. Universidad Nacional de Córdoba. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Investigaciones Biológicas y Tecnológicas; Argentina.